HUBUNGAN ANTARA PERSONALITI DENGAN KECERDASAN EMOSI DALAM KALANGAN MAHASISWA DI UNIVERSITI TEKNOLOGI MALAYSIA (UTM), SKUDAI JOHOR - A. Razif, Umi Kalthum; Aripin, Siti Nazurulaina (Jurnal 'Ulwan, 2023)
Student usually feel various emotions during the process of learning knowledge. If they not have a strong personality to handle certain situations, their emotions might be out of their control. Therefore, they might be difficult to adapt to the increasingly challenging educational environment. Hence, the main purpose of this study was conducted to identify whether personality affects emotional intelligence. This survey was carried out on 110 female students and 105 male students majoring in Mathematical Sciences, Faculty of Science, University of Technology Malaysia (UTM) by handing out questionnaire. There are two questionnaires used in this study includes Junior Eysenck Personality Inventory (JEPI) for personality variables while Goleman's Emotional Intelligence Inventory (1995) is used to test emotional intelligence variables. Next, the data obtained through this study had been analyzed using the Statistical Package for Social Science (SPSS) version 25.0. The research findings stated that there is a significant relationship between personality and emotional intelligence [r = 0.970, p < 0.05) and gender [t (213) = -2.892, p < 0.05]. Nevertheless, the age and race of the students did not affect their emotional intelligence where each got results [F (2) = 0.644, p > 0.05] and [F (3) = 0.257, p > 0.05].